Experimental Models of Autoimmune Demyelinating Diseases in Nonhuman Primates. Issue 1 (January 2018) - Stimmer, Lev; Fovet, Claire-Maëlle; Serguera, Ché
Human idiopathic inflammatory demyelinating diseases (IIDD) are a heterogeneous group of autoimmune inflammatory and demyelinating disorders of the central nervous system (CNS). These include multiple sclerosis (MS), the most common chronic IIDD, but also rarer disorders such as acute disseminated encephalomyelitis (ADEM) and neuromyelitis optica (NMO). Great efforts have been made to understand the pathophysiology of MS, leading to the development of a few effective treatments. Nonetheless, IIDD still require a better understanding of the causes and underlying mechanisms to implement more effective therapies and diagnostic methods. Experimental autoimmune encephalomyelitis (EAE) is a commonly used animal model to study the pathophysiology of IIDD. EAE is principally induced through immunization with myelin antigens combined with immune-activating adjuvants. Nonhuman primates (NHP), the phylogenetically closest relatives of humans, challenged by similar microorganisms as other primates may recapitulate comparable immune responses to that of humans. In this review, the authors describe EAE models in 3 NHP species: rhesus macaques ( Macaca mulatta ), cynomolgus macaques ( Macaca fascicularis ), and common marmosets ( Callithrix jacchus ), evaluating their respective contribution to the understanding of human IIDD. EAE in NHP is a heterogeneous disease, including acute monophasic and chronic polyphasic forms. This diversity makes it a versatile model to use in translational research. This clinical variability also creates an opportunity to explore multiple facets of immune-mediated mechanisms of neuro-inflammation and demyelination as well as intrinsic protective mechanisms. Here, the authors review current insights into the pathogenesis and immunopathological mechanisms implicated in the development of EAE in NHP.